Blind Watchers of PSI: A Rebuttal of Reber and Alcock (2019) - Carr, Bernard (Journal of Scientific Exploration, 2019)
Parapsychology will only be accepted as part of mainstream science if physics can be extended to accommodate at least some so-called psychic phenomena. This paper disagrees with the argument of Reber and Alcock that these phenomena can be excluded a priori because they are incompatible with physics. On the other hand, it agrees with their claim that the phenomena cannot be explained in terms of current physics (eg. relativity theory and quantum theory). Rather one needs an extension of physics which amalgamates these theories, this being an aim of mainstream physics anyway, with the new theory also linking to consciousness if this is regarded as a fundamental rather than incidental feature of the universe. One possible extension involves the idea that perceptual space and physical space are amalgamated as part of a 5-dimensional reality structure, the extra dimension being associated with mental (rather than physical) time. Such a model may be required to accommodate even normal mind and incorporating further dimensions might then allow some paranormal phenomena. This could also relate to the extra dimensions invoked in some models of particle physics.